Efektivitas Penggunaan Media Interaktif dalam Pembelajaran Matematika di Sekolah Dasar - Hardian Muhammad; Intan Putri Lusita; Intan Yumeriza; Kartila Pri Malti; Meiliana Fitria Ningrum; Salsabila Zorin; Nana Fauzana Azima (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Mathematics is often viewed by many elementary school students as a difficult subject. This is because if it is only taught in the lecture method, the material is abstract and not very interesting. To overcome this, the use of interactive learning media is a promising solution. The purpose of this study was to determine the extent to which interactive media affects mathematics learning outcomes in elementary school and what factors support its success. The method used is literature study research by collecting and analyzing various related research findings. The findings of this study indicate that interactive media such as animation, educational applications, digital games and other visual media can help to better understand the material, increase enthusiasm for learning, and promote active participation in the learning process. In addition, most of the studies analyzed showed an increase in students' academic reviews after using interactive media compared to traditional learning methods. The success of using this media is also greatly influenced by teacher motivation, institutions available at school, and the suitability of the media to student needs. Therefore, it is important for teachers to choose the right media and remain innovative. This will make the mathematics learning process more interesting and easier for students.